Problems identification and improvement path of China’s marine ecological compensation legal system - Wang, Tao (Frontiers in Marine Science, 2023)
In China's marine industry, which has been growing quickly over the past few years, marine ecological compensation has been a critical issue. The goal of this paper is to find the problems in China's legal system for marine ecological compensation and to suggest ways to make it better. The study found that institutional supply shortage lead to lack of coordination and dispersion in China’s marine ecological compensation legislative system. The absence of c legislative concept of “land-sea overall planning” in China’s marine ecological compensation legal system is another major issue. And there is lack of clear standards for marine ecological compensation as well. Apart from that, marine ecological compensation in China mainly depends on government financial allocation, including financial transfer payments and subsidies. However, due to the low degree of market compensation, there is a need to improve the compensation method and standard. The paper suggests that China should establish a comprehensive marine ecological compensation system that includes both government and market-based mechanisms. Additionally, it is recommended that China should strengthen its legal framework for marine ecological compensation by clarifying the responsibilities of relevant departments and improving the transparency of information disclosure. Overall, this paper provides valuable insights into the identification of problems and improvement path of China's marine ecological compensation legal system, which can contribute to better protection of marine ecology in China.